Pre-purchase screening for Coxiella burnetii in small ruminants: farm acceptance and field evaluation identify the ex-vivo interferon-γ assay as a promising tool - Matthijs, Anneleen; Claine, François; Simons, Xavier; Soares, Ana; Desqueper, Damien; Van Mael, Eva; Mori, Marcella (Frontiers in Veterinary Science, 2025)
IntroductionQ fever, caused by Coxiella burnetii, is a disease posing significant zoonotic risk and economic impact, particularly in small ruminants. Screening prior to flock introduction is essential for disease control and prevention, especially in breeding males, given their potential role in pathogen transmission.MethodsThis study combined a survey of small ruminant farmers with a field evaluation to explore the feasibility of pre-purchase screening and to compare the performance of four diagnostic tests: real-time qPCR, antibody ELISA, intradermal testing, and an ex-vivo interferon-gamma (IFN-γ) recall assay.ResultsThe survey (n = 114) revealed widespread gaps in health status awareness and a lack of pre-screening during animal lending or borrowing, with regional differences, although most farmers supported pre-purchase screening. The field evaluation across ten farms (five positive and five negative) showed that the IFN-γ recall assay provided diagnostic accuracy comparable to ELISA (DSe: 0.80 vs. 0.74; DSp: 0.94 vs. 0.96), with higher positivity rates among unvaccinated animals (n = 122; 42.6% vs. 26.2%). The assay also proved feasible for field use, with a 24-hour antigen stimulation protocol performing equally good as the 48-hour version (AUC: 0.99 vs. 0.98). Real-time qPCR and intradermal testing showed the least utility under field conditions.DiscussionOverall, the IFN-γ recall assay emerges as a promising diagnostic tool for detecting C. burnetii infection in small ruminants, particularly in settings where vaccination history is unknown or incomplete.